2016
DOI: 10.5430/jnep.v6n12p131
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Australian and Spanish nursing students for intimate partner violence

Abstract: Objective: Throughout the world intimate partner violence (IPV) is a significant issue and it is important that nurses contribute to policy development, as well as to the nursing care of families. Nurses are uniquely positioned to identify, and support women experiencing IPV. For them to contribute to policy development, they need firstly to develop a better understanding of the issue and to their role in addressing it. This study explored and compared perceptions, attitudes and knowledge of IPV of nursing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Another reason could be the positive impact of media in Saudi Arabia on community attitudes towards domestic violence and women's rights (AlJuhani & AlAteeq, 2020). Studies from Spain (Gorman et al, 2016) and India (Gandhi et al, 2018) have reported that nursing students' attitudes towards IPV and knowledge of IPV were positively influenced by exposure to media.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be the positive impact of media in Saudi Arabia on community attitudes towards domestic violence and women's rights (AlJuhani & AlAteeq, 2020). Studies from Spain (Gorman et al, 2016) and India (Gandhi et al, 2018) have reported that nursing students' attitudes towards IPV and knowledge of IPV were positively influenced by exposure to media.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is critical that nurses have a solid understanding of IPV, the associated health problems, presenting problems and symptoms, and the skills to identify and care for women subjected to IPV (Crombie, Hooker & Reisenhofer, 2016;Di Giacomo, Cavallo, Bagnasco, Sartini & Sasso, 2017;Tambağ & Turan, 2015). Although the importance of such education for nurses at pre and post-registration levels has been recommended and guidelines developed by the WHO (2013aWHO ( , 2013bWHO ( , 2017, the nursing curricula in many countries are lacking content related to IPV (AbuTaleb, Dashti, Alasfour, Elshazly & Kamel, 2012;Beccaria et al, 2013;Bradbury-Jones & Broadhurst, 2015;Clark, Renner & Logeais, 2017;Crombie et al, 2016;Doran & Hutchinson, 2016;Gorman et al, 2016;Hutchinson et al, 2019;Lovi, Hurley & Hutchinson, 2018); Sundborg, Saleh-Stattin, Wändell & Törnkvist, 2012). Some of the effective strategies to IPV-related education include: using interactive learning opportunities (Bradbury-Jones & Broadhurst, 2015;Wyatt, McClelland & Spangaro, 2019), providing experiential learning with simulated patients for students to gain confidence in screening for IPV (Blumling, Kameg, Cline, Szpak & Koller, 2018;Gomez-Fernandez, Goberna-Tricas & Paya-Sanchez, 2017;Johnson & Montgomery, 2017;Tufts, Klements & Karlowicz, 2009), improving communication skills using role plays (Zachor, Chang, Zelazny, Jones & Miller, 2018), having adequate time and space (Lovi et al, 2018) to address nurses' attitudes towards and stereotypical assumptions about IPV and the victims and perpetrators (Baird, Saito, Eustace & Creedy, 2018;Di Giacomo et al, 2017;Doran & Hutchinson, 2016;Rigol-Cuadra, Galbany-Estragué & Fuentes-Pumarola, 2015), focus on women-centered, compassionate and supportive care…”
Section: Introductionmentioning
confidence: 99%